Diagnosis and Management of Cirrhosis-Related Osteoporosis - Santos, Lï¿½via Alves Amaral [UNESP]; Romeiro, Fernando Gomes [UNESP] (Wiley, 2016)
Management of cirrhosis complications has greatly improved, increasing survival and quality of life of the patients. Despite that, some of these complications are still overlooked and scarcely treated, particularly those that are not related to the liver. This is the case of osteoporosis, the only cirrhosis complication that is not solved after liver transplantation, because bone loss often increases after immunosuppressant therapy. In this review, the definitions of bone conditions in cirrhotic patients are analyzed, focusing on the more common ones and on those that have the largest impact on this population. Risk factors, physiopathology, diagnosis, screening strategies, and treatment of osteoporosis in cirrhotic patients are discussed, presenting the more striking data on this issue. Therapies used for particular conditions, such as primary biliary cirrhosis and liver transplantation, are also presented.